2018
DOI: 10.1111/apha.13159
|View full text |Cite
|
Sign up to set email alerts
|

Protective roles of estradiol against vascular oxidative stress in ovariectomized female rats exposed to normoxia or intermittent hypoxia

Abstract: E -based therapy could help prevent the vascular consequences of CIH in apneic women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 61 publications
3
16
2
2
Order By: Relevance
“…However, only the ERα agonist prevented the increase of arterial blood pressure during exposure to CIH. These results are in line with our recent study showing that E 2 treatment prevents oxidative stress in the brain cortex, adrenal medulla, and in the thoracic aorta of ovariectomized female rats exposed to a similar pattern of CIH.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, only the ERα agonist prevented the increase of arterial blood pressure during exposure to CIH. These results are in line with our recent study showing that E 2 treatment prevents oxidative stress in the brain cortex, adrenal medulla, and in the thoracic aorta of ovariectomized female rats exposed to a similar pattern of CIH.…”
Section: Discussionsupporting
confidence: 93%
“…In contradistinction with these previous findings, current results show that under exposure to CIH, PPT and DPN do not increase the activity of complex IV, but rather prevent the reduction of complex I activity. We have recently reported that in the thoracic aorta of ovariectomized female rats the effects of E 2 on pro‐ and antioxidant enzyme activities are different under normoxic and CIH conditions . Therefore, it is possible that the discrepancy observed between the present results and those reported by Irwin et al may be accounted for by the CIH exposures in our study.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, Prog does not prevent the CIH‐induced increase in arterial blood pressure. These results complement our previous dataset showing the role of E 2 (Laouafa et al., 2017; Ribon‐Demars et al., 2018) and selective agonists of E 2 receptors (Laouafa et al., 2019) on oxidative stress, respiratory irregularities and arterial blood pressure in a similar experimental design.…”
Section: Discussionsupporting
confidence: 90%
“…Oxidative stress in CIH‐exposed animals and sleep apnoea patients is thought to have several harmful consequences, including high activity of the sympathetic nervous system (driven by peripheral chemoreceptors), arterial hypertension, cardiovascular diseases and neuronal damage (Almendros et al., 2014; Lavie, 2015; Prabhakar et al., 2015). In line with a rich literature showing antioxidant properties of E 2 , we have demonstrated that in female rats exposed to CIH, E 2 supplementation prevented the elevation of arterial blood pressure and oxidative stress damage in the brain cortex, brainstem (Laouafa et al., 2017) and thoracic aorta (Ribon‐Demars et al., 2018). Furthermore selective agonists of the E 2 α and β receptors (ERα and ERβ) prevented the elevation of mitochondrial ROS production during CIH exposure, but only the ERα agonist prevented the increase of arterial blood pressure (Laouafa et al., 2019).…”
Section: Introductionsupporting
confidence: 84%